Constructing Meaning: A Critical Reflection on Phonetics and Phonology Teaching Learning in EFL Higher Education Context - Andriani, Agis; Pertamana, Dede; Rosmala, Dewi; Izzati, Aina Amalia (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Language knowledge and presentation skills are part of the essential characteristics that an English tutor must possess. However, in reality, a tutor who identifies as a non-native English speaker is not really able to be an adequate model for English language learning coupled with many traditional methods that fail to meet the diverse needs of students, for example not utilizing modern technological tools effectively, and sometimes tutors do not have sufficient awareness of pedagogical knowledge and linguistic knowledge to be a role model of English in the EFL context. Through critical reflection using the 3 Whats model, this research explores how the learning process inspires and motivates students to become English education students, who are designed to become future teachers. 136 English education students were involved in writing a critical reflection after the lecture of Phonetics and Phonology Subject lecture for one semester ended. The findings show that the tutor has the capacity assessed in nine criteria of ideal language teachers, namely having competence, liking English when teaching, motivating, consistently giving feedback, facilitating students to show their abilities, innovating to overcome students' difficulties, appreciating students' work, and being professional in whatever they do. Therefore, further investigation is needed to explore how technology impacts in building of students' critical language awareness.